EVALUATION ON THE STATUS OF THE WETLAND RESOURCES (MAINLY NYPAPALM) IN THE LOWER RIVER-ESTUARY OF THU BON (QUANG NAM PROVINCE) AND SOLUTIONS FOR MANAGEMENT, PROTECTION AND REHABILITATION - Dai, Nguyen Huu; Macintosh, Donald (Vietnam Journal of Marine Science and Technology, 2008)
The lower river-estuaty of Thu Bon, Hoi An Town, with more than 1200 hectares of wetlands, covered by mangrove trees (Nypa palm) and seagrasses. These mangrove and seagrass ecosystems played an important role to the environment and aquatic resources not only for Hoi An Town, but also for Cu Lao Cham Marine Protected Area. The studied results show that about 80 hectares of Nypa wetlands and 30 hectares of seagrass beds occur mainly in Cam Thanh commune. Nypa palms are being managed and reasonably exploited for demand of construction materials, but seagrass beds were seriously reduced by several destroyed fishing ways. About 300 hectares of wetlands area in Cam Thanh commune were proposed to manage, restore and conserve.